Association of thyroid hormone sensitivity indicators with visceral fat area in euthyroid overweight/obese type 2 diabetes patients: sex differences - Ma, Xuan; Zhou, Qingyi; Ma, Chen; Sheng, Jie; Jiang, Xinghe; Gao, Guanqi; Ji, Baolan (Frontiers in Endocrinology, 2025)
AimsThyroid hormone (TH) sensitivity plays a key role in glucose and lipid metabolism. However, its relationship with visceral fat distribution in euthyroid overweight/obese patients with type 2 diabetes mellitus (T2DM) remains unclear. This study aimed to examine the associations between TH sensitivity indices and visceral fat area (VFA), with particular attention to sex-specific differences.MethodsA total of 831 euthyroid overweight/obese T2DM patients (374 males and 457 females) were enrolled. Multiple TH sensitivity indices were calculated. VFA was measured by bioelectrical impedance analysis (BIA), and visceral fat obesity (VFO) was defined as VFA ≥ 100 cm². Associations were assessed using univariate and multivariate linear and logistic regression models, adjusting for age, BMI, and glycemic control parameters.ResultsIn males, TFQIFT3 was independently associated with VFA (β = 0.088, P < 0.05) and predicted VFO (OR: 2.545; 95% CI: 1.206–5.370, P = 0.014). In females, no significant associations were observed between TH sensitivity indices and either VFA or VFO, indicating a clear sex-specific difference.ConclusionsTFQIFT3 may serve as a potential marker linking thyroid hormone sensitivity with visceral fat accumulation, particularly in male T2DM patients.